Assessment of the relation between obesity, serum lipids, and dietary intake of vegetable oils - Viral R Dave; Rujul P Shukla; Sudip Bhavsar; Nirmika Patel; Kantibhai N Sonaliya (Wolters Kluwer Medknow Publications, 2020)
Introduction: The study was conducted to assess the association between consumption of particular variety of cooking oil and its effect on serum lipid profile and also on body mass index (BMI). Material and Methods: The study was conducted at one of the tertiary care hospitals, Ahmedabad city, India. Patients with ≥18 years age who were undergoing "lipid profile" test at central laboratory department of selected hospital and giving consent were the study participants. Details of serum lipid profile were taken from report along with which anthropometric measurements were done and details of diet were taken. Data were entered into MS Excel and were analyzed by frequency, contingency coefficient, and Fisher's exact test. Results: Total 1000 participants were included in the study, among which 274 (27.4%) had raised lipid levels and 729 (72.9%) were preobese or obese. Association between variety of cooking oil used and cholesterol-high-density lipoprotein ratio revealed contingency coefficient value of 0.042 with P value of 0.416. Association between BMI and variety of cooking oil used revealed Fisher's exact value as 83.015 with P < 0.001. Conclusion: Statistical association was not found between serum lipid profile and type of oil used for cooking. Obesity indices revealed significant statistical association with both variety of cooking oil used and serum lipid profile. Dyslipidemia was found to have statistical significant association with raised blood pressure and raised blood glucose.